2006
DOI: 10.1021/jp065412u
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Reactive Intermediates Formed in Acetaldehyde under Exposure to Low-Energy Electrons

Abstract: Chemical reactions have been induced in condensed acetaldehyde by exposure to low-energy electrons as demonstrated by use of high-resolution electron energy loss (HREEL) spectroscopy and thermal desorption spectroscopy (TDS). The HREEL spectra show that the acetaldehyde film is modified significantly when the incident electron energy is increased above 10 eV. Release of CO upon exposure to electrons at an incident energy of 14 eV is observed by electronic HREEL spectra. The changes in the vibrational spectra u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 27 publications
6
18
1
Order By: Relevance
“…To provide complementary information on electron stimulated reaction mechanisms, growth processes, and the influence of irradiation time on the film’s structure, separate experiments were performed under ultrahigh vacuum (UHV) on nanometer scale thick 1,2-DAP films. The value of this UHV experimental approach to probe electron-mediated processes has been demonstrated in recent studies relevant to atmospheric chemistry, astrochemistry, , astrobiology, thin film modification, and radiation damage to biologically relevant molecules. ,, …”
Section: Introductionmentioning
confidence: 98%
“…To provide complementary information on electron stimulated reaction mechanisms, growth processes, and the influence of irradiation time on the film’s structure, separate experiments were performed under ultrahigh vacuum (UHV) on nanometer scale thick 1,2-DAP films. The value of this UHV experimental approach to probe electron-mediated processes has been demonstrated in recent studies relevant to atmospheric chemistry, astrochemistry, , astrobiology, thin film modification, and radiation damage to biologically relevant molecules. ,, …”
Section: Introductionmentioning
confidence: 98%
“…[57] In the solid phase, only limited studies were conducted. [58] On the other hand, electron spin resonance (ESR) studies of solid acetaldehyde in noble gas matrices at 77 K exposed to high energy electrons (1 MeV) revealed acetyl (CH3ĊO) to be the dominating radical. [59] This was supported by another ESR study of acetaldehyde isolated in freon matrices after irradiation with -radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, the effects of electrons on the adsorbed molecules can be monitored in situ using surface analytical techniques. Indeed, this experimental approach has been successfully employed in a number of recent studies designed to examine electron mediated processes relevant to atmospheric chemistry, astrobiology, the modification of organic films including self-assembled monolayers, and radiation damage to biologically relevant molecules. ,, In regard to electron stimulated reactions of organometallic precursors, Yates et al have studied the effect of low-energy (2−27 eV) electrons on the decomposition of hexafluoracetylacetonate Cu(I) vinyltrimethylsilane, a metal−organic chemical vapor deposition (MOCVD) precursor used for the deposition of copper, on the Si(7 × 7) surface at room temperature . X-ray photoelectron spectroscopy (XPS) results showed that electron stimulated reactions led to the formation of Cu(0) while the threshold for decomposition was ≈4 eV, consistent with a dissociative electron attachment mechanism.…”
Section: Introductionmentioning
confidence: 99%